Rotavirus and the web: analysis of online conversations in Italy during 2020 - Federico Marchetti; Sara Verazza; Margherita Brambilla; Vincenzo Restivo (Taylor & Francis Group, 2022)
Rotavirus is the most common cause of severe diarrhea among children worldwide. In 2017, Italy included rotavirus vaccination in its National Immunization Program. The use of social media monitoring, an efficient tool to understand vaccine hesitancy, has increased in recent years; however, only a few examples of such monitoring are available for Italy. Present study analyzed content on online sources, including social media, to identify factors contributing to Italian parents' decisions to vaccinate or not their children against rotavirus. Blogmeter Suite was used to search and analyze conversations related to rotavirus in Italian on online sources during 2020. These data were compared with data from 2019. There were 2250 mentions of "rotavirus" recorded; 1080 were related to the rotavirus vaccine. Terms and hashtags used were similar in both years. Facebook was the main source of influence, Instagram dominated the engagement (the sum of interactions related to a post), and Google Trends showed a 5-year upward trend in searches for rotavirus vaccine. Of 1270 sentiment opinions, 60.7% were negative. More parents were familiar with the disease and the vaccine in 2020 compared with 2019. Pediatricians were the most influential healthcare professionals (59.2% of mentions), followed by vaccination staff (33.4%). The most relevant factors for vaccine hesitancy were fear of adverse events, concerns about the vaccination schedule, and COVID-19. Present study represents the first web listening analysis of online discussions about rotavirus. The results can be used to inform targeted communication to counteract misinformation and raise awareness about rotavirus vaccination among parents.